2014
DOI: 10.4161/mabs.29601
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach to investigate the effect of methionine oxidation on pharmacokinetic properties of therapeutic antibodies

Abstract: Preserving the chemical and structural integrity of therapeutic antibodies during manufacturing and storage is a major challenge during pharmaceutical development. Oxidation of Fc methionines Met252 and Met428 is frequently observed, which leads to reduced affinity to FcRn and faster plasma clearance if present at high levels. Because oxidation occurs in both positions simultaneously, their individual contribution to the concomitant changes in pharmacokinetic properties has not been clearly established. A nove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
102
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 95 publications
(113 citation statements)
references
References 49 publications
8
102
1
Order By: Relevance
“…We did not measure a significant decrease in affinity at pH 6 or in fraction bound at neutral pH on FcRn after methionine Ox, whereas other publications 20, 21, 22, 23 indicate that FcRn binding is reduced upon methionine Ox (only studied at pH 6). However, highest Ox levels that we induced were around 7%, whereas other groups report differences in FcRn binding at levels close to 80% of methionine Ox.…”
Section: Resultscontrasting
confidence: 73%
See 1 more Smart Citation
“…We did not measure a significant decrease in affinity at pH 6 or in fraction bound at neutral pH on FcRn after methionine Ox, whereas other publications 20, 21, 22, 23 indicate that FcRn binding is reduced upon methionine Ox (only studied at pH 6). However, highest Ox levels that we induced were around 7%, whereas other groups report differences in FcRn binding at levels close to 80% of methionine Ox.…”
Section: Resultscontrasting
confidence: 73%
“…Stracke et al . 21 found that only one of the two heavy chains is oxidized when Ox levels are around 50% or lower, and the other heavy chain of the antibody is still able to bind to FcRn. This agrees well with our results as no impact is measured at 7% Ox.…”
Section: Resultsmentioning
confidence: 99%
“…Only molecules with both heavy chains oxidized at M252 show a significantly faster clearance whereas a single oxidized M252 per antibody exhibits no significant effect. [84] …”
Section: Methionine Oxidationmentioning
confidence: 99%
“…Later research, however, suggests that while oxidation of M252 has a considerable impact on binding toward FcRn, oxidation of M428 seems to play a less important role and might even counteract the effect of M252. [84] Additionally, it seems as if the number of oxidized M252 residues on the individual molecule is of decisive importance for the effect on FcRn binding and pharmacokinetics. Only molecules with both heavy chains oxidized at M252 show a significantly faster clearance whereas a single oxidized M252 per antibody exhibits no significant effect.…”
Section: Methionine Oxidationmentioning
confidence: 99%
“…9,23,24 Recently, a clear effect of Met oxidation in the constant region of an IgG1 on the pharmacokinetics has been reported in 2 independent in vivo studies. 13,25 For large biomolecules such as recombinant antibodies, bottom-up liquid chromatography-mass spectrometry (LC-MS) of proteolytic peptides is often the method of choice for monitoring site-specific oxidation reactions. 2,5,[9][10][11][12][13]17,19,22,26 However, advances in native mass spectrometry has enabled the analysis of intact protein and protein complexes under more physiological conditions.…”
Section: Introductionmentioning
confidence: 99%